Unveiling the Complex Role of Exosomes in Alzheimer’s Disease - Sun M; Chen Z (Dove Medical Press, 2024)
Mingyue Sun, Zhuoyou Chen Department of Neurology, The Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University, Changzhou, 213000, People's Republic of ChinaCorrespondence: Zhuoyou Chen, Email neuro1972@163.comAbstract: Alzheimer's disease (AD) is the most common neurodegenerative illness, characterized by memory loss and cognitive decline, accounting for 60- 80% of dementia cases. AD is characterized by senile plaques made up of amyloid β (Aβ) protein, intracellular neurofibrillary tangles caused by hyperphosphorylation of tau protein linked with microtubules, and neuronal loss. Currently, therapeutic treatments and nanotechnological developments are effective in treating the symptoms of AD, but a cure for the illness has not yet been found. Recently, the increased study of extracellular vesicles (EVs) has led to a growing awareness of their significant involvement in neurodegenerative disorders, including AD. Exosomes are small extracellular vesicles that transport various components including messenger RNAs, non-coding RNAs, proteins, lipids, DNA, and other bioactive compounds from one cell to another, facilitating information transmission and material movement. There is growing evidence indicating that exosomes have complex functions in AD. Exosomes may have a dual role in Alzheimer's disease by contributing to neuronal death and also helping to alleviate the pathological progression of the disease. Therefore, the primary aim of this review is to outline the updated understandings on exosomes biogenesis and many functions of exosomes in the generation, conveyance, distribution, and elimination of hazardous proteins related to Alzheimer's disease. This review is intended to provide novel insights for understanding the development, specific treatment, and early detection of Alzheimer's disease.Keywords: Alzheimer's disease, exosomes, pathogenesis, diagnosis, treatment